2015
DOI: 10.3892/or.2015.4141
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis of microRNAs and downregulated miR-486-5p and miR-30a-5p in non-small cell lung cancer

Abstract: Abstract. Lung cancer is the leading cause of cancer-related mortality worldwide and although there have been improvements in treatment there is a low survival rate. The aim of the present study was to investigate the effect of microRNA (miRNA) on cell pathways. A miRNA microarray was used to profile miRNAs of lung cancer tissues. It was identified that 33 miRNAs with >2.0-fold change and FDR <0.05 were differentially expressed between the adjacent noncancerous lung tissues and non-small cell lung cancers NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…Notably, miR-30a-5p has been implicated in many types of human malignancies. For instance, miR-30a-5p is overexpressed in glioma (11) but significantly downregulated in lung cancer (12). Accordingly, miR-30a-5p serves different roles in different types of cancer (11,12), and its functions require full elucidation in different cancer types including HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, miR-30a-5p has been implicated in many types of human malignancies. For instance, miR-30a-5p is overexpressed in glioma (11) but significantly downregulated in lung cancer (12). Accordingly, miR-30a-5p serves different roles in different types of cancer (11,12), and its functions require full elucidation in different cancer types including HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al suggested that miR-486-5p could be a biomarker and play a suppressor gene in NSCLC [19]. Some studies have also shown the effect of miR-486-5p on inhibition of the development and growth of NSCLC in mouse models [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-486-5p is significantly downregulated in NSCLC [19], breast cancer [20], hepatocellular carcinoma [21], chronic kidney disease [22], spinal cord injury [23], and Duchenne muscular dystrophy (DMD) [24]. Based on this correlation, we hypothesized that miR-486-5p may play an important role in tumorigenesis and tumor development in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…ANK1 is a host gene for miR-486 [162] which in turn is a source of two mature miR-486 miRNAs, namely, miR-486-3p and miR-486-5p [163]. Importantly, ANK1 hypermethylation inhibits the transcription of miR-486 [164], which may have pathogenic consequences as suppression of this miRNA has pro-inflammatory consequences and is furthermore associated with increased cellular survival and proliferation [165,166]. Furthermore, upregulation of miR-486 acts as a negative regulator of Akt (protein kinase B), mTOR and STAT3 (signal transducer and activator of transcription 3), all of which play major roles in microglial activation, proliferation and survival [167,168].…”
Section: Epigenetic Dysregulation Of Ank1 As a Source Of Microglial Pmentioning
confidence: 99%